Digital Transformation of Government: A Study of E-Government in Asean Countries - L.M. Azhar Sa'ban; Anwar Sadat; Rasid Pora; Jornie Lumintao (LPPM Universitas PGRI Sumatera Barat, 2026)
The development of information and communication technology (ICT) has driven the digital transformation of government, with e-government becoming the main instrument for improving bureaucratic efficiency, quality of public services, transparency, and community participation. In ASEAN countries, the implementation of e-government varies significantly, with Singapore leading the way, while Cambodia, Myanmar, and Laos are still in the early stages of development. This study aims to analyze trends in scientific publications on e-government in Asean countries between 2014-2024 using a bibliometric approach. Data were obtained using Publish or Perish software from the Scopus database, then analyzed and visualized using VOSviewer. The results of the study show that 2020 was the peak of productivity with the highest number of publications and citations, especially related to the adoption of digital services during the Covid-19 pandemic. Indonesia and Thailand were recorded as the countries with the largest contribution to publications, while Singapore dominated in the implementation of e-government practices. The main focus of the study was still on the issues of digital transformation and information and communication technology, with the theme of innovation covering digital transformation. These findings confirm that the success of e-government is greatly influenced by the readiness of digital infrastructure, public literacy, human resource capacity, and government commitment. This study contributes by providing a comprehensive overview of the dynamics of e-government research in Asean countries.